TRENDS AND IMPACTS OF CHILD MARRIAGE IN A PSYCHOLOGICAL PERSPECTIVES (Case Study in Tuban Regency) - Siti Fatimah (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
Child marriage is a marriage carried out by someone who has not yet entered a mature or mature age in thinking, emotionally, biologically and psychologically. The age of marriage is explained in law No. 16 of 2019 on amendments to law No. 1 article 7 of 1974, namely marriage is only permitted if a man and a woman reach the age of 19 (nineteen) years. Child marriage in Tuban district has been a trend for the past 3 years and continues to increase due to the impact of the Covid 19 pandemic which has paralyzed several sectors of life. The economic sector is the biggest factor because of the impact of the Covid pandemic, many parents have been laid off and have dropped out of work. By marrying off the child, the responsibility of the parents will be reduced. This is the reason why child marriage is increasing day by day. Law No. 16 of 2019 is a breath of fresh air for life, because the age law has a very large effect on children's rights to life so that they grow and develop according to their age, prevent domestic violence, prevent dropping out of school and also improve maternal and child health. child. This research uses descriptive qualitative research with interview methods of various groups of people based on what is happening in the community with the aim of knowing the reasons for early marriages in Tuban Regency. The results showed that the reasons for early marriage in Tuban district were 1) economic factors 2) educational factors 3) customs factors 4) promiscuity factors